Analisis Faktor-Faktor yang Memengaruhi Kepatuhan Wajib Pajak Orang Pribadi di Kabupaten Kebumen - Tri Wahyu Ningrum; Fajar Satriya Segarawasesa (CV. ULIL ALBAB CORP, 2023)
This study aims to examine and analyze the effect of tax amnesty, e-filing, taxpayer awareness, and tax sanctions on individual taxpayer compliance in Kebumen Regency. This study applied a quantitative approach. The population in this study was 477,110 individual taxpayers. The sample used in this study was 100 individual taxpayers in Kebumen Regency. The technique for determining the number of samples in this study used the slovin formula. Data collection techniques employed a questionnaire. Methods of data analysis used multiple linear regression analysis with the SPSS 26 program. This research concluded that tax amnesty and e-filing had no effect on individual taxpayer compliance. Meanwhile, taxpayer awareness and tax sanctions had a positive effect on individual taxpayer compliance.